Financial Inclusion, Ethical Investment, And Corporate Social Responsibility: A Comprehensive Analysis Of Factors Affecting Sustainable Finance In Indonesian MSMEs - D. Iwan Riswandi; Agung Zulfikri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are essential to the Indonesian economy, yet they frequently encounter obstacles when trying to obtain financing and implement ethical business practices. This study looks into how MSME performance and sustainable financing in Indonesia are affected by financial inclusion, ethical investing, and corporate social responsibility (CSR). Using survey data from 287 Indonesian MSMEs, Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis is used quantitatively. The findings show a strong positive correlation between sustainable finance, CSR, ethical investing, financial inclusion, and MSME performance. More specifically, enhanced MSME performance and sustainable finance outcomes are linked to increased financial inclusion, ethical investing practices, and participation in CSR initiatives. These results highlight the significance of encouraging equitable and conscientious approaches to economic growth to improve the competitiveness and long-term viability of MSMEs in Indonesia.